“Actitud y grado de conocimiento sobre el SIDA en los estudiantes de tres colegios estatales del cuarto y quinto año de secundaria del distrito de yurimaguas de noviembre 1999 a octubre 2000” - Noriega Morey, Marco Adolfo (1999)
Them diseases of transmission Sexual (ETS), follow a trend upward in Latin America specifically in the Peru and the risk of transmission is greater between the class poor, playing so them knowledge and attitudes a role very important in the prevention of them same; for what was this study in order to determine the degree of knowledge and identify sexually transmitted diseases attitudes among students of colleges No. 0756 district of Pinto Recodo, province of Lamas (rural area) and the Colegio Ofelia Velasquez in the district de Tarapoto province of San Martín (urban area). A comparative study was conducted by making use of the method of survey and interview, collecting data on a prospective basis, analyzing and interpreting data using techniques descriptive statistics and inference!. Indeed, determined the degree of knowledge of students of ambos.colegios and attitudes identified ado...